Bibliometric Analysis of Wastewater Biological Nitrogen Removal Externally Added Carbon Sources Based on Web of Science and CNKI Databases - Huang, Yuanming; Peng, Jinmei; Liu, Siqi; Chen, Siyuan; Ning, Xinqiang (International Journal of Natural Resources and Environmental Studies, 2024)
To investigate the research hotspots and development status of wastewater biological denitrification with externally added carbon sources, based on the Web of Science Core Collection database and CNKI Resource Library, we used the visualization software CiteSpace to visualize and analyze the authors, countries, institutions and keywords of the articles published in the field of wastewater biological denitrification with externally added carbon sources in the period of 2000-2022, and then analyze their distribution and research hotspots. The results show that the mainstream journals in the field of water environment at home and abroad have paid great attention to the carbon neutrality of wastewater treatment, and the nitrogen and carbon source of wastewater has become a research hotspot in the field of water environment. This study summarizes the current categories of new carbon sources and predicts the feasibility of using waste from the brewing industry as an additional carbon source. It provides a theoretical basis for promoting the resource utilization of waste in the brewing industry.